3(7x-1)=5(3x+3)

Simple and best practice solution for 3(7x-1)=5(3x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7x-1)=5(3x+3) equation:


Simplifying
3(7x + -1) = 5(3x + 3)

Reorder the terms:
3(-1 + 7x) = 5(3x + 3)
(-1 * 3 + 7x * 3) = 5(3x + 3)
(-3 + 21x) = 5(3x + 3)

Reorder the terms:
-3 + 21x = 5(3 + 3x)
-3 + 21x = (3 * 5 + 3x * 5)
-3 + 21x = (15 + 15x)

Solving
-3 + 21x = 15 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-3 + 21x + -15x = 15 + 15x + -15x

Combine like terms: 21x + -15x = 6x
-3 + 6x = 15 + 15x + -15x

Combine like terms: 15x + -15x = 0
-3 + 6x = 15 + 0
-3 + 6x = 15

Add '3' to each side of the equation.
-3 + 3 + 6x = 15 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = 15 + 3
6x = 15 + 3

Combine like terms: 15 + 3 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 25=2c-9 | | 9x-4(3x-2)=4 | | 5x=2(x+30) | | 3b+15=27 | | m+2=15 | | 9x-19=7x+11 | | 15x^3+25x^2-60x= | | 8t-11=5t+19 | | -2(18-3t)=7y+2y | | -(5y+2)-(-4y-8)=1 | | 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 |

Equations solver categories